1996
DOI: 10.1159/000147785
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Transforming Growth Factor-Alpha in Suckling Porcine Intestine

Abstract: The distribution of transforming growth factor-alpha (TGFα), a member of the epidermal growth factor (EGF) family, was studied immunohistochemically in small intestinal tissues of suckling pigs which were 7, 14 and 21 days of age. TGFα immunostaining was similar in villous epithelium in all intestinal regions of all ages examined, and was diffuse throughout the epithelial cytoplasm and more prominent in the apical and brush-border regions of the cells. Cytoplasmic immunoreactive TGFα was also identified in cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Immunohistochemical localization of TGF-α in porcine intestine showed that expression is greater at PD14 and 21 than in PD7 piglets (37). TGF-α belongs to the EGF family and binds to the EGF receptor (37). If TGFα regulates EGF receptor expression significantly, its decrease by PD14 may be explained.…”
Section: Articlesmentioning
confidence: 98%
See 1 more Smart Citation
“…Immunohistochemical localization of TGF-α in porcine intestine showed that expression is greater at PD14 and 21 than in PD7 piglets (37). TGF-α belongs to the EGF family and binds to the EGF receptor (37). If TGFα regulates EGF receptor expression significantly, its decrease by PD14 may be explained.…”
Section: Articlesmentioning
confidence: 98%
“…A study on rat duodenum found that endogenous TGF-β1 production is low at birth, but increases after mid-weaning (36). Immunohistochemical localization of TGF-α in porcine intestine showed that expression is greater at PD14 and 21 than in PD7 piglets (37). TGF-α belongs to the EGF family and binds to the EGF receptor (37).…”
Section: Articlesmentioning
confidence: 99%
“…TGF-a stimulates proliferation of rat intestinal tissue during the developmental period (48). TGF-a immunoreactive protein is present in the small intestinal crypt epithelium in suckling pigs (49). TGF-a and TGF-b play a role in the repair of the intestine after phytohemagglutinin-induced acute epithelial injury (47).…”
Section: Clinical Learning Pointmentioning
confidence: 99%